Conflictological Model of Institutionalization of Economic Processes in the Agriculture - Halyna Pohrishchuk (UIKTEN, 2021)
The institutional essence, structure and typology of conflicts in a market economy are determined. The components of typical conflicts have been studied, as well as analysis of the type of economic conflicts "power – business entities" in the agricultural sector. It is established that any disproportions of the socio-economic system lead, due to the relevant incidents, to the aggravation of conflict situations. It was found that the conflict situations are objectively based on the contradictions of the interests of the main groups of agents and, accordingly, the institutions of the system. The results of our research give grounds to assert that the institutional modernization of the agricultural sector is possible only if new types are prevented and the consequences of existing conflicts are reduced, which is a kind of scheme of evasion within public control. It is proved that one of the universal tools of the unobserved economy in the light of the conflict paradigm are certain types of institutional agreements, and this is a fundamentally new methodology for reflecting real processes.